2021
DOI: 10.1007/s42485-021-00065-y
|View full text |Cite
|
Sign up to set email alerts
|

Discovering mycobacterial lectins as potential drug targets and vaccine candidates for tuberculosis treatment: a theoretical approach

Abstract: M. tuberculosis proliferates within the macrophages during infection and they are bounded by carbohydrates in the cell wall, called lectins. Despite their surface localization, the studies on exact functions of lectins are unexplored. Hence, in our study, using insilico approaches, 11 potential lectins of Mtb was explored as potential drug targets and vaccine candidates. Initially, a gene interaction network was constructed for the 11 potential lectins and identified its functional partners. A gene ontology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Because lectins are present on the surface of mycobacterial cells, they can be easily recognized by immune cells so that lectins can be used as potential vaccine candidates. Several studies have shown binding epitopes of MHC-I and MHC-II to mycobacterial lectins (Sundar et al 2021). A DNA vaccine from Rv1419 has been successfully developed and can induce a weaker humoral immune response and a stronger cellular immune response in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Because lectins are present on the surface of mycobacterial cells, they can be easily recognized by immune cells so that lectins can be used as potential vaccine candidates. Several studies have shown binding epitopes of MHC-I and MHC-II to mycobacterial lectins (Sundar et al 2021). A DNA vaccine from Rv1419 has been successfully developed and can induce a weaker humoral immune response and a stronger cellular immune response in mice.…”
Section: Discussionmentioning
confidence: 99%